An unusual case of recurrent cutaneous carcinomas over extragenital multicentric pigmented bowen's disease - Suvidha D Kamath; M Ramesh Bhat; Nisha J Marla; Sukumar Dandekeri; Michelle Fernandes; Jacintha Martis (Indian Dermatology Online Journal, 2024)
Bowen's disease is a slowly progressive squamous cell carcinoma (SSC) in situ with high potential for malignant transformation. In this case, we describe a patient with multicentric Bowen's disease for the past 26 years, developing growths over his left buttock. The patient had a previous history of growth developing over his right thigh, and was diagnosed with metatypical basal cell carcinoma (BCC). The points that make this case noteworthy are recurrent cutaneous carcinomas over the multicentric generalized occurrence of in situ SCC of extragenital type, the rarity of the site, and the nature of its morphological presentation in the skin of color.